Determination of Production Instrumentation Equipment Maintenance Intervals In the Paper Industry - Nurma M. Hidayatulloh; Tedjo Sukmono (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2020)
PT. XYZ is a manufacturing industry engaged in paper processing with afval raw materials. The problem faced is machine failure that occurs suddenly without predictability, this is because there is no scheduled maintenance (preventive main-tenance). The object of this research is focused on production instrumentation equipment. This study uses the Failure Mode and Effect Analyzer (FMEA) method to identify the causes of failure and the effects of these failures by determining the critical value of the component, namely the Risk Priority Number (RPN) which is the largest, then the Reliability Centered Maintenance (RCM) II Decision Worsheet method for determine maintenance intervals of production instrumentation equipment. Based on the results of RPN calculations in the FMEA method to determine the critical components of the Instrumentation equipment, namely the Control Valve, it can be seen that the highest total RPN value is found in three components, namely Restrictor with an RPN value of 390, Power Supply with RPN of 297, and also a Pilot Positioner. with an RPN value of 240. And with optimum maintenance intervals, among others, the Restrictor every 40 hours, the Power Supply every 41 hours, and the Pilot Positioner every 47 hours.